Long wavelength quantum cascade laser and gas sensing application - Li, Yishun (Nanyang Technological University, 2023)
Since the establishment of the theoretical concept of the Quantum Cascade Laser in the 1970s, this innovative new type of semiconductor laser has been through significant development. Different from traditional semiconductor lasers, beam generation of the quantum cascade laser is based on quantum mechanical phenomena. A noticeable advantage of the quantum cascade laser is the high wavelength tunability. By manipulating the design in quantum wells and barriers, the Quantum Cascade Laser can achieve specific absorption spectrum that allows for a wide range of applications. Another benefit for the quantum cascade laser is its high output power with significantly improved power efficiency, allowing for highly focused beam facilitating its application in biological or material science. The major goal of this dissertation is to investigate the performance of mid-infrared laser upon gas sensing. First, we reviewed recent literature about the history of semiconductor lasers and discussed the advantages of quantum cascade lasers. To compare the performance of several different designs of quantum cascade lasers, we simulated distinct designs of laser structures and characterized the performance by measuring the light-current-voltage and spectral characteristics. We found that the waveguide structure of the laser is the major factor that determines quantum cascade laser performance. Factors that impact the waveguide structures include structure optimization as well as the device fabrication process. As a conclusion, based on our findings in the elements that are essential for laser performance, we discussed recent development tendency in this field and assess the further direction of the quantum cascade laser design. We emphasized that specific designs for the waveguide structure will be the most important aspect to consider when applying the quantum cascade laser in spectroscopy, environmental monitoring, or other applications.